Revisiting, in vivo, the hair regreasing process by the Sebuprint method. Issue 1 (25th July 2018) - Gao, J.; Liu, C.; Zhang, S.; Techer, M. P.; Bouabbache, S.; Pouradier, F.; Panhard, S.
Abstract: Background: The regreasing process of hair by sebum is daily observed by consumers. Methods to investigate this phenomenon were scarcely updated since the 1990s, despite the constant progresses in hair cleaning procedures or shampoo formulations. Our objective was first, to develop an in vivo noninvasive method for quantifying the spread of sebum along the hair shaft. Secondly, we use this new method to define the overall kinetics of the hair‐regreasing process among two cohorts of Chinese men with opposite self‐perceptions of their scalp/hair greasiness (ie, greasy or not greasy). Material and methods: One hundred and twenty‐three Chinese men (aged 18‐35 years) participated to the study. The technique used basically adapts the Sebumeter™ technology where supple polymer films are applied onto and along the hair shaft. The sampled hair sebum is further quantified by image analysis/increased transparency. Results: The technique developed showed an adequate reproducibility under fixed conditions (pressure, investigators, scalp sites, etc.). In the two cohorts of subjects (eg, greasy, nongreasy), hair regreasing process was found sharing a same linear progression with time. The two cohorts of men presented significantly different values in the total amount of spread sebum by an approximately two‐fold coefficient, with however comparable average values in the sebum amount present at the root region 48 hours post shampoo. At such timing, the spread of sebum reaches much longer distances in the greasy scalp cohort. Conclusion: This technique appears promising for assessing the efficacy of cosmetic ingredients (or products) that aim at delaying a natural process that is daily and negatively perceived by consumers.